BREAK-EVEN POINT (BEP) ANALYSIS OF THE IMPACT OF PAYMENT METHODS AND SALES VOLUME ON HEIHO HEALTHY FOOD CATERING BUSINESS IN DEPOK, 2024 - Sri Fitria Jayusman; Lienda Millania Ladya; Mutawaqil Bilah Tumanggor; Suhaila Husna Samosir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Advances in digital technology have encouraged small and medium-sized enterprises (SMEs) to shift to cashless payment systems, including the Quick Response Code Indonesian Standard (QRIS). This study aims to assess the effect of QRIS implementation on the cost structure, profitability, and break-even point (BEP) of Heiho Healthy Food Catering in Depok in 2024. The method used is BEP analysis, taking into account an additional cost of 0.3% in the form of the Merchant Discount Rate (MDR) for QRIS transactions. The results show that before implementing QRIS, the contribution margin per unit was IDR 21,451.61 with a BEP of 3,131 units. After using QRIS without any adjustment to the selling price, the margin decreased to IDR 21,296.77, and the BEP increased to 3,155 units, indicating a higher risk to profitability if sales decline. However, increasing the selling price by 0.3% to IDR 50,150 per unit raised the margin to IDR 21,446.77, and the BEP decreased to 3,134 units, approaching the level before QRIS implementation. The findings indicate that QRIS can still generate profit, provided that it is accompanied by an appropriate pricing adjustment strategy to maintain margins and business efficiency.